Systematic Literature Review of Mathematics Learning Strategies for Children with Special Educational Needs - Tata Rahmasari; Imam Sujadi; Diari Indriati; Farida Nurhasanah (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Learning mathematics for children with special needs requires an approach that is tailored to the type and needs of each student. This literature review aims to find out about mathematics learning strategies for children with special needs. This literature study presents a literature review of mathematics learning strategies and how they are implemented, including the types of children with special needs, the topics discussed and the level of education of the children with special needs. The literature study method used was SLR (Systematic Literature Review) with the process of selecting articles for SLR referring to the PRISMA flow chart for the period 2020-2024, considering that the literature on learning strategies for children with special needs continues to grow. Data were collected from Web of Science and Scopus databases, and 10 relevant articles from 2020 to 2024 were selected and analysed. The results revealed that from the 10 literatures, it was found that learning strategies must be adapted to the type of special needs that students have. The strategies vary from video modelling, virtual manipulatives, to STEAM and inquiry-based learning, all of which aim to help children with disabilities master mathematical concepts that were previously considered difficult.